Envolvimento dos receptores centrais angiotensinérgicos e mineralocorticóides no aumento do apetite ao sódio induzido por privação hídrica em ratos com hipertensão renovascular - Lucera, Gabriela Maria (2020)
Sodium appetite in normotensive rats submitted to water deprivation (WD) for 24 h followed by 2 h with access to water only (partial rehydration–PR) depends on the activation of the renin-angiotensin system (RAS). Two-kidney-1-clip (2K1C) rats show a hyperactivation of the renin-angiotensin-aldosterone system (RAAS) and an increase in sodium intake induced by WD-PR. Therefore, the aim of the present study were: 1) to verify the participation of angiotensin II (ANG II) receptors in sodium intake induced by WD in 2K1C rats; 2) to verify the participation aldosterone (ALDO) receptors in sodium intake during WD in 2K1C rats, 3) to verify if there is a synergism between ANG II and ALDO in sodium intake during WD in 2K1C rats. For this end, we used Hotlzman male rats (initial weight 150-180 g) to induce renovascular hypertension and sham surgery. A guide cannula was implanted in the lateral ventricle (LV) in both groups after 6 weeks of renal surgery. To distinguish thirst and sodium appetite, 5 days after implant recovery, 2K1C and sham rats were submitted to WD-PR protocol with LV injections of vehicle (1% ethanol in saline, 2 μl) or saline (0.15 M NaCl), RU28318 (100 ng/2 μl) or losartan (66 ug/1 μl), and to verify synergism, administration of RU+losartan or vehicle+saline were perfomed 10 min apart in a group of rats. After 3 days the tests were counterbalanced in each group. The blockade of ANG II AT1 receptors reduced water intake during thirst test in sham and 2K1C rats, which as not observed during the blockade of ALDO mineralocorticoid receptors (MR). Simultaneous blockade of the two receptors reduced water intake in sham and 2K1C rats during the thirst test. The 0.3 M NaCl intake was partially reduced during the sodium appetite test with AT1 receptors blockade in 2K1C rats. A similar effect was observed with the blockade of MR receptor in 2K1C rats. Double receptor blockade completely blocked sodium appetite in 2K1C rats. These results show that the sodium appetite induce by WD in 2K1C rats is mediated by the activation of the AT1 and MR, possibly by a greater activation of the RAAS, and that ANG II and ALDO have a synergism to induce sodium appetite in 2K1C rats.